PROSPECTS FOR THE EFFECTIVE USE OF COMPETITIVE ADVANTAGES OF SMALL BUSINESS ENTITIES - Otajanov Umid Abdullayevich (Journal of Artificial Intelligence and Digital Economy, 2024)
In the article, a mechanism for the development of small business entities, ensuring the competitiveness of small business entities and ensuring that small business entities have competitive advantages is proposed, and in order to evaluate their level, a multifactor model of the production volume of a small business entity is determined based on econometric analyzes and forecast results are developed based on it. developed